Esophageal rupture: a severe complication of transesophageal echocardiography - Fernando Peixoto Ferraz de Campos; Brenda Margatho Ramos Martines; João Augusto Santos Martines; José de Arimatéia Batista Araújo Filho (University of São Paulo, 2012)
Since when the first transesophageal echocardiography (TEE) was undertaken in 1975, technological advances have made this diagnostic modality more reliable. TEE indications became widespread in cardiac and non-cardiac surgeries, intensive care units, and ambulatory clinics. The procedure is generally considered a safe diagnostic tool, but occasionally complications do occur. The insertion and manipulation of the ultrasound probe can cause oropharyngeal, esophageal, or gastric trauma. Although rare, these complications may present a mortality rate of up to 56% depending on the treatment approach and the elapsed time to the diagnosis. The authors report a case of a 65-year-old woman submitted to attempt a TEE in order to better study or diagnose an inter-atrial communication. After 3 days of the procedure, the patient was admitted to the hospital with edema, hyperemia of the anterior face of the neck, accompanied by systemic symptoms. The imaging diagnostic work-up evidenced signs of esophageal rupture and upper mediastinal involvement, the former confirmed by upper gastrointestinal endoscopy. The patient was treated with antibiotics and cervical and mediastinal drainage, with a favorable outcome.